2014
DOI: 10.1074/jbc.m114.561472
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Ablation of Protein Kinase A (PKA)-mediated Cardiac Troponin I Phosphorylation Leads to Excitation-Contraction Uncoupling and Diastolic Dysfunction in a Knock-in Mouse Model of Hypertrophic Cardiomyopathy

Abstract: Background:The R21C mutation in cardiac troponin I (cTnI) prevents PKA-mediated phosphorylation of serines 23 and 24 of cTnI in vivo. Results: Myofilament function is uncoupled from the intracellular [Ca 2ϩ ] and delays muscle relaxation. Conclusion: Long term ablation of cTnI phosphorylation leads to hypertrophy, diastolic dysfunction, and dysautonomia in mice. Significance: Restoration of phosphorylated cTnI may prevent hypertrophic cardiomyopathy and diastolic dysfunction.The cardiac troponin I (cTnI) R21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 81 publications
2
27
0
Order By: Relevance
“…cTnI-R21C knock-in mice showed diastolic dysfunction with delayed Ca 2+ re-sequestration (Dweck et al, 2014), a phenotype that supports the role of the N-terminal extension of cTnI in the regulation of diastolic function of the heart.…”
Section: Pathogenic Mutationsmentioning
confidence: 78%
“…cTnI-R21C knock-in mice showed diastolic dysfunction with delayed Ca 2+ re-sequestration (Dweck et al, 2014), a phenotype that supports the role of the N-terminal extension of cTnI in the regulation of diastolic function of the heart.…”
Section: Pathogenic Mutationsmentioning
confidence: 78%
“…Dweck et al . found that the isolated cardiac myocytes from R21C transgenic mice (with ages older than 12 months) significantly delayed Ca 2+ transient decay and relaxation [158]. The phenotype of cTnI R21C mutation supports the regulatory role of cTnI N-terminus in diastolic function of the heart.…”
Section: Ctn Mutations Associated With Familial Hypertrophic Cardiomymentioning
confidence: 88%
“…Importantly, both mutants blunted the ability of PKA to reduce K C-I and pCa 50 and speed relaxation of myofibrils [125]. It is worth mentioning that cTnI R21C disrupts the PKA phosphorylation on S23/S24 of cTnI [30, 158, 185], and thus results in a “blunted” β-adrenergic stimulation response, which may be the actual physiologic/pathogenic mechanism of cTnI R21C . Therefore, to further understand whether it is the cTnI R21C per se that is altering function or just the inability to get S23/S24 phosphorylated, we introduced the bis -phosphomimic substitutions S23D/S24D into cTnI R21C (cTnI R21C/S23D/S24D ) to mimic effect of PKA phosphorylation.…”
Section: The Relationship Between Ctnc-ctni Interaction and The Bluntmentioning
confidence: 99%
“…1933 Recently, we also reported the blunted β-adrenergic response for both cTnI HCM-associated mutations. 34,35 Both mutations significantly left-shifted (increased) Ca 2+ binding affinity to cTn ( K Ca ) and the affinity of cTnC for cTnI ( K C–I ).…”
Section: Introductionmentioning
confidence: 85%